Hydraulic research for successful fish migration improvement - ?nature-like? fishways = Badania hydrauliczne dla poprawy warunków migracji ryb - przepławki ?bliskie naturze? - Teppel, Angelika; Tymiński, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents an overview of the design solutions for fishways which are locates nearby hydrotechnical constructions. Currently fashionable and recommended hydraulic design of fishways are moving towards "close to nature" solutions. Their characteristic feature is applicable to the construction a natural building materials (tree trunks, stones, gravel, vegetation) in such a way that its appearance resembled a small natural water courses.
Keywords: przepławki dla ryb; warunki hydrauliczne; przepływ wody; model testowy; fish ladders; water flow; hydraulic conditions; model test